Fatal intracranial haemorrhage occurring after oral anticoagulant treatment initiation for secondary stroke prevention in patients with atrial fibrillation. (17th May 2020) - Tsivgoulis, G.; Katsanos, A. H.; Seiffge, D. J.; Paciaroni, M.; Wilson, D.; Koga, M.; Macha, K.; Cappellari, M.; Kallmünzer, B.; Polymeris, A. A.; Toyoda, K.; Caso, V.; et al.
Abstract : Background and purpose: In this pooled analysis of seven multicentre cohorts potential differences were investigated in the incidence, characteristics and outcomes between intracranial haemorrhages (ICHs) associated with the use of non‐vitamin K antagonist oral anticoagulants (NOAC‐ICH) or with vitamin K antagonists (VKA‐ICH) in ischaemic stroke patients after oral anticoagulant treatment initiation for atrial fibrillation (AF). Methods: Data from 4912 eligible AF patients who were admitted in a stroke unit with ischaemic stroke or transient ischaemic attack and who were treated with either VKAs or NOACs within 3 months post‐stroke were included. Fatal ICH was defined as death occurring during the first 30 days after ICH onset. A meta‐analysis of available observational studies reporting 30‐day mortality rates from NOAC‐ICH or VKA‐ICH onset was additionally performed. Results: During 5970 patient‐years of follow‐up 71 participants had an ICH, of whom 20 were NOAC‐ICH and 51 VKA‐ICH. Patients in the two groups had comparable baseline characteristics, except for the higher prevalence of kidney disease in VKA‐ICH patients. There was a non‐significant higher number of fatal ICH in patients with VKAs (11 events per 3385 patient‐years) than in those with NOACs (three events per 2623 patient‐years; hazard ratio 0.32, 95% confidence interval 0.09–1.14). Three‐month functional outcomes were similar ( P > 0.2) in the two groups. The meta‐analysis showed a lower 30‐day mortality risk for patients with NOAC‐ICH compared to VKA‐ICH (relative risk 0.70, 95% confidence interval 0.51–0.95). Conclusions: Non‐vitamin K oral anticoagulants for intracranial haemorrhages and VKA‐ICH occurring during secondary stroke prevention of AF patients have comparable baseline characteristics and outcomes except for the risk of fatal ICH within 30 days, which might be greater in VKA‐ICH.